Angiotensin II AT2 receptor ligands with phenylthiazole scaffolds. (1st July 2022) - Gopalan, Greeshma; Palo-Nieto, Carlos; Petersen, Nadia N.; Hallberg, Mathias; Larhed, Mats
Graphical abstract: Abstract: The syntheses and the AT1 R and AT2 R binding data of a series of new small molecule ligands are reported. These ligands comprise a phenylthiazole scaffold rather than the biphenyl or phenylthiophene scaffolds found in essentially all of the previously described ligands originating from the nonselective AT1 R/AT2 R ligand L-162, 313 and the AT2 R selective agonist C21, the latter now in Phase II/III clinical trials. A phenylthiazole rather than the phenylthiophene scaffold that is present in the AT2 R selective agonist C21 and in the AT2 R selective antagonist C38 had a deleterious effect on the affinity to AT2 R. Nevertheless, a significant improvement could be accomplished by introduction of a small bulky alkyl group in the 2-position of the imidazole ring attached through a methylene group bridge to the phenylthiazole scaffold. Hence, a combination of a 2- tert -butyl or a 2-isopropyl group and a butoxycarbonyl furnished potent AT2 R selective ligands. Furthermore, a high affinity ligand derived from L-162, 313 and exhibiting a > 35 fold selectivity for AT1 R was identified (10 ). The ligand 21 with the 2- tert -butyl group and ∼ 35 fold selectivity for AT2 R, demonstrated high stability in human, rat and mouse liver microsomes and a very attractive profile with regard to the inhibition of common drug-metabolizing CYP enzymes. Thus, very low levels of inhibition of CYP 3A (5%), 2D6 (12%), 2C8 (26%), 2C9 (23%) and 2B6 (24%) were observed with the 2- tert -butyl derivative comprising the methoxycarbonyl sulfonamide function, levels that are significantly lower than those obtained with C21 under the same experimental conditions.